Relationship Between Accounting Earnings of Listed Companies in The Stock Exchange of Thailand and Gross Domestic Product of Thailand - Kanei, Pritchaya; Sarapaivanich, Naruanrd; Siriwan, Twoangtip; Laohavisudhi, Suvanna (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2022)
The objective of this study was to study the relationship between the accounting earnings of listed companies in The Stock Exchange of Thailand and the gross domestic product of Thailand. This study collected data from the database of the Stock Exchange of Thailand, Bank of Thailand, and the Office of the National Economic and Social Development Council from 1999 to 2020. The total of datasets, was 81 datasets, was used for the analysis. Statistical analysis was multiple regression analysis. The dependent variable is the gross domestic product change rate in the next quarter. The independent variables are aggregate net profit in the current quarter and net profit change rate in the current quarter. The control variables are public debt, average exchange rate, interest rate, and unemployment rate. The results showed that aggregate net profit in the current quarter and net profit change rate in the current quarter had a significant positive correlation with gross domestic product change rate in the next quarter. It was also found that public debt, average exchange rate and unemployment rate were related to the gross domestic product change rate in the next quarter. This result of the study will be the recommendations for of the Stock Exchange of Thailand, Bank of Thailand, and the Office of the National Economic and Social Development Council in terms of the accounting earnings of listed companies in The Stock Exchange of Thailand and the gross domestic product of Thailand as well as public debt, average exchange rate, interest rate, and unemployment rate.